2019
DOI: 10.1021/jacs.9b10474
|View full text |Cite
|
Sign up to set email alerts
|

Chemoenzymatic o-Quinone Methide Formation

Abstract: Generation of reactive intermediates and interception of these fleeting species under physiological conditions is a common strategy employed by Nature to build molecular complexity. However, selective formation of these species under mild conditions using classical synthetic techniques is an outstanding challenge. Here, we demonstrate the utility of biocatalysis in generating o-quinone methide intermediates with precise chemoselectivity under mild, aqueous conditions. Specifically, α-ketoglutarate-dependent no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 60 publications
2
48
0
Order By: Relevance
“…To generate the target diol in the absence of TropC, a biocatalytic approach was employed using CitB and TropB. 21,27,[38][39][40] We aimed to directly synthesize diol 13 through oxidative dearomatization of benzylic alcohol 25 using TropB. Notably, trihydroxybenzaldehyde 18 was detected in these reactions, but diol intermediate 13 was not observed, suggesting that the fragmentation reaction described in Path 3 (Figure 1D) occurs spontaneously under the reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…To generate the target diol in the absence of TropC, a biocatalytic approach was employed using CitB and TropB. 21,27,[38][39][40] We aimed to directly synthesize diol 13 through oxidative dearomatization of benzylic alcohol 25 using TropB. Notably, trihydroxybenzaldehyde 18 was detected in these reactions, but diol intermediate 13 was not observed, suggesting that the fragmentation reaction described in Path 3 (Figure 1D) occurs spontaneously under the reaction conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[197][198][199] Chemoenzymatic approaches have also proved useful in the synthesis of natural products. [200][201][202][203] A recent important publication by Lipshutz and coworkers has shown that the formation of micelles in the reaction medium can facilitate the combination of chemo-and bio-catalysis in a single reactor as the substrates, products and catalysts partition into the different compartments. 204 For an extensive review of the recent literature on biocatalytic cascade reactions see Kroutil and coworkers.…”
Section: Integration: Biocatalytic and Chemoenzymatic Cascade Processesmentioning
confidence: 99%
“…Regioselective DA cycloaddition attributed to proper orientation and approach of reacting partner's diene and dienophile. In this regards, quinone methide intermediates and their derivatives are a versatile synthon and are well explored to access diversified and functionalized naphthoquinone derivatives [128,129] . In line, Carneiro disclosed an experimental and computational techniques to the regioselective synthesis of naturally occurring α ‐ and β ‐lapachone in 2020 [130] .…”
Section: Selectivity In Diels‐alder Cycloaddition Pathwaymentioning
confidence: 99%
“…In this regards, quinone methide intermediates and their derivatives are a versatile synthon and are well explored to access diversified and functionalized naphthoquinone derivatives. [128,129] In line, Carneiro disclosed an experimental and computational techniques to the regioselective synthesis of naturally occurring αand β-lapachone in 2020. [130] The formation of αand β-lapachones, was a noteworthy feature of their discovery, as many natural products and bioactive molecules could be synthesized due to its incredible capacity to create both the regioisomers.…”
Section: Selectivity Influence By Intrinsic Parameters Pertaining Die...mentioning
confidence: 99%